2022
DOI: 10.22302/iccri.jur.pelitaperkebunan.v38i3.521
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding for Identification of Helopeltis sp. from Kaliwining Experimental Station using Mitochondrial COI Gene

Abstract: Helopeltis sp. is one of the major pests of the cocoa plant. Helopeltis can decrease cocoa yield by 50 to 60%. Several species of Helopeltis spp. are still often misidentified due to similarity in morphology such as size and color. This study aimed to identify Helopeltis sp. through DNA barcoding using the mitochondrial cyto- chrome C oxidase subunit 1 (COI) gene. Analysis was carried out on 100 adults Helopeltis sp. from Kaliwining Experimental Station, Indonesian Coffee and Cocoa Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…After that, adaptation of additional insect species occurs relatively rarely, unless the planting area is notably increased. Pancaningtyas et al (2022) examined Helopeltis molecularly in Kaliwining and found that the species belongs to H. bradyi. Two kinds of Helopeltis that attack cocoa in Indonesia are Helopeltis theivora and H. antonii (van Hall, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…After that, adaptation of additional insect species occurs relatively rarely, unless the planting area is notably increased. Pancaningtyas et al (2022) examined Helopeltis molecularly in Kaliwining and found that the species belongs to H. bradyi. Two kinds of Helopeltis that attack cocoa in Indonesia are Helopeltis theivora and H. antonii (van Hall, 1994).…”
Section: Introductionmentioning
confidence: 99%